CHARACTERISTICS OF BAGASSE BIOCHAR IN INDUSTRIAL SCALE PRODUCTION - Kuncara, Jaka; Setyawan, Martomo; Hakika, Dhias Cahya (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2024)
Bagasse is a waste that can still be processed into more useful materials, in this case it will be processed into biochar. The bagasse used is sugarcane milling waste from a sugar factory in Majalengka, Cirebon, West Java. The pyrolysis process is carried out at the biochar factory of PT XXX which is also located in the area. Making biochar with an industrial-scale pyrolysis reactor namely the rotary carbonization furnace reactor. The main components are a bagasse feeder system, rotary drum dryer, pyrolysis reactor, fan and condenser. The system operates in line from the feeder to the biochar output. The purpose of this research is to investigate the pyrolysis of bagasse in a rotary horizontal carbonization furnace reactor to study the effect of pyrolysis process parameters in the form of temperature and residence time on the product characteristics of biochar. The tests provided results that the residence time has an effect on the proximate and ultimate analysis of biochar. The results showed that with increasing residence time, the volatile meter, hydrogen and oxygen decreased while the ash content, fixed carbon, carbon and gross calories increased. The test also provides results that temperature affects the proximate and ultimate analysis of biochar. The results show that as the pyrolysis temperature increases, the parameters of ash content, fixed carbon and gross calory increase while the parameters of volatile metter, hydrogen and oxygen decrease. The morphological structure of biochar changes with increasing pyrolysis temperature and the results showed that the higher the pyrolysis temperature, the larger the diameter of the biochar pores.